2013
DOI: 10.9724/kfcs.2013.29.5.479
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Quality Characteristics of Sulgidduk by the Addition of Persimmon Peel

Abstract: This study is to examine nutrients in the persimmon peel develop processed products and analyze their quality properties. The persimmon peel powder was rich in nutrients with 4.35% of moisture, 3.01% of protein, 1.02% of lipid, 2.02% of ash and 5.7 °Brix of Sugar concentration as well as 82.5 mg% of total carotenoid. As far as quality properties of Sulgidduk were concerned when the 5% addition persimmon peel resulted in the highest level of watery content and the more colors were added the lower the L value be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A decrease in the general acceptance of biscuits with an increase in the level of potato peel powder is due to the total effect on taste, color and texture because they are the basic qualities that influence consumer acceptance. Han et al [19] reported that replacement of wheat flour with potato peels in different proportions (10%, 15% and 20%) led to a decrease in a degree of biscuit hardness in all studies samples. Cohesiveness, springiness and brittleness increased in the samples with the 10% replacement rate and decreased is all other samples compared to the control.…”
Section: Sensory Properties Of the Studied Biscuit Samplesmentioning
confidence: 85%
See 2 more Smart Citations
“…A decrease in the general acceptance of biscuits with an increase in the level of potato peel powder is due to the total effect on taste, color and texture because they are the basic qualities that influence consumer acceptance. Han et al [19] reported that replacement of wheat flour with potato peels in different proportions (10%, 15% and 20%) led to a decrease in a degree of biscuit hardness in all studies samples. Cohesiveness, springiness and brittleness increased in the samples with the 10% replacement rate and decreased is all other samples compared to the control.…”
Section: Sensory Properties Of the Studied Biscuit Samplesmentioning
confidence: 85%
“…A decrease in the values of yellowness (b*) and brightness (L*) was due to browning [51]. Han et al [19] indicated that replacement of wheat flour with potato peel in different proportions led to higher brightness (L*) values (90.97, 89.24 and 90.04) and lower a* (4.69, 5.13 and 3.85) and b* values (-9.49, -7.68 and -10.66) in the biscuit samples with the 10%, 15% and 20% replacement ratio, respectively, compared to the corresponding values of color indices in the control biscuits (83.88, 8.92 and 1.25, respectively).…”
Section: Color Indicators Of the Studied Biscuit Samplesmentioning
confidence: 99%
See 1 more Smart Citation